Psychometric properties of the Chinese version of multidimensional scale of perceived social support - Yang, Xiujun; Xue, Minxia; Pauen, Sabina; He, Huawu (Psychology research and behavior management, 2024)
The Chinese version of the MSPSS has good reliability and validity, and is suitable for Chinese college students.